Rupture Model of the M5.8 Pawnee, Oklahoma, Earthquake From Regional and Teleseismic Waveforms. Issue 5 (7th March 2019) - Moschetti, M. P.; Hartzell, S. H.; Herrmann, R. B.
Abstract: The 2016 M 5.8 Pawnee, Oklahoma, earthquake is the largest earthquake to have been induced by wastewater disposal. We infer the coseismic slip history from analysis of apparent source time functions and inversion of regional and teleseismic P waveforms, using aftershocks as empirical Green's functions. The earthquake nucleated on the shallow part of the fault, initially rupturing toward the surface, followed shortly thereafter by slip deeper on the fault. Deeper slip occurred below the aftershocks and at greater depths than most induced seismicity in the region, suggesting that small‐ to moderate‐sized earthquakes may not occur on deeper parts of faults in Oklahoma because they are further from failure than shallower fault sections. Comparisons with models of pore pressure perturbations further suggest that the earthquake may have initiated within a region of higher pore pressure perturbation but was not confined to this zone. These observations inform source physics and understanding of maximum magnitudes. Plain Language Summary: We analyzed seismic recordings from the 2016 M 5.8 Pawnee, Oklahoma, earthquake to examine how the earthquake ruptured in time and how slip occurred on different parts of the fault. Our results show that the earthquake started on the shallow part of the fault, followed by slip toward the surface and slip occurring on the deeper part of the fault. By comparing our results with a previous study of changes in pore fluid pressures caused by injection, we find that the earthquake may have started where pore pressures were affected, but that the earthquake process continued outside of this region. That earthquake rupture can extend outside of the areas directly affected by injection processes is important for understanding maximum magnitudes from induced earthquakes. Key Points: Earthquake rupture initiated on the shallow part of the fault, then ruptured toward the surface and on deeper parts of the fault Coseismic slip occurs at greater depths than do the aftershocks and the vast majority of regional seismicity Pore fluids may have influenced the earthquake nucleation and shallow slip, but are unlikely to have influenced deep rupture